2008
DOI: 10.1111/j.1349-7006.2008.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

CBR1 and CBR3 pharmacogenetics and their influence on doxorubicin disposition in Asian breast cancer patients

Abstract: The present study aimed to identify polymorphic genes encoding carbonyl reductases (CBR1, CBR3) and investigate their influence on doxorubicin disposition in Asian breast cancer patients (n = 62). Doxorubicin (60 mg/m 2 ) was administered every 3 weeks for four to six cycles and the pharmacokinetic parameters were estimated using non-compartmental analysis (WinNonlin). The Mann-Whitney U-test was used to assess genotypic-phenotypic correlations. (1) The phase I and II enzymes are expressed abundantly in hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
3
35
1
5
Order By: Relevance
“…Genetic polymorphisms of these metabolic enzymes are reportedly related to the PK of several anticancer agents [16][17][18]. CBR-1 D2 diplotypes tagged by at least one variant allele at the CBR-1 c.627C [ T and ?967G [ A loci are correlated with significantly higher exposure levels of doxorubicin, suggesting the possibility that the intracellular conversion to doxorubicinol is reduced in Asian patients with breast cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms of these metabolic enzymes are reportedly related to the PK of several anticancer agents [16][17][18]. CBR-1 D2 diplotypes tagged by at least one variant allele at the CBR-1 c.627C [ T and ?967G [ A loci are correlated with significantly higher exposure levels of doxorubicin, suggesting the possibility that the intracellular conversion to doxorubicinol is reduced in Asian patients with breast cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional regulation of the CBR3 gene may affect the physiologic role of CBR3, since molecular mechanisms that regulate an enzyme's expression are often closely related to its function. CBR1 1096G>A (rs9024) and CBR3 730G>A (rs1056892) were tested for their probable association with the efficacy of doxorubicin chemotherapy efficacy in previous studies of breast cancer patients [19]. Fan et al [20] (2008) reported that polymorphisms in CBR3 may explain the interindividual and interethnic variability of doxorubicin pharmacokinetics and pharmacodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The interindividual differences in carbonyl reductase activity may in part reflect variable rates of CBR1 gene transcription which was revealed to be regulated by the aryl hydrocarbon receptor (AhR) pathway [46,47]. Further, CBR1 polymorphism is suspected to play a role in variable CBR1 activity and expression since CBR1 polymorphisms were detected to be associated with various CBR1 expression levels or isoforms with distinct enzymatic properties [44,48,49].…”
Section: Cbr1 21 Introductionmentioning
confidence: 95%